2020
DOI: 10.1155/2020/4646029
|View full text |Cite
|
Sign up to set email alerts
|

YQFM Alleviates Side Effects Caused by Dasatinib through the ROCK/MLC Pathway in Mice

Abstract: Dasatinib, as a second-generation broad-spectrum tyrosine kinase inhibitor, presents an antitumor effect by inhibiting tyrosine kinases. However, dasatinib causes serious side effects, such as gastrointestinal bleeding and liver toxicity, possibly through the activation of ROCK kinase and MLC phosphorylation. At present, there is no effective prevention and treatment method. Previous research studies have shown that YQFM (YiQiFuMai powder injection) protects the blood-brain barrier by inhibiting the ROCK/MLC s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…23 At a very high dose (≥50 mg/kg), dasatinib increases vascular leakage in the unchallenged small intestine and spleen of mice via activation of ROCK and subsequent myosin light chain phosphorylation inside endothelial cells, leading to downregulation of VE-cadherin and other associated junctional molecules. 7,24 In agreement with this, our pilot study demonstrated that high doses of dasatinib (25 and 50 mg/kg) induced severe intestinal bleeding in mice within 24 h but no vascular leakage was observed in the wound area (data not shown). These factors may contribute to adverse events following dasatinib treatment.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…23 At a very high dose (≥50 mg/kg), dasatinib increases vascular leakage in the unchallenged small intestine and spleen of mice via activation of ROCK and subsequent myosin light chain phosphorylation inside endothelial cells, leading to downregulation of VE-cadherin and other associated junctional molecules. 7,24 In agreement with this, our pilot study demonstrated that high doses of dasatinib (25 and 50 mg/kg) induced severe intestinal bleeding in mice within 24 h but no vascular leakage was observed in the wound area (data not shown). These factors may contribute to adverse events following dasatinib treatment.…”
Section: Discussionsupporting
confidence: 80%
“…In rats, intraperitoneal administration of dasatinib (10 mg/kg) daily for 8 weeks leads to pleural effusion by producing a reactive oxygen species (ROS)‐induced increase in endothelial permeability, but not by inhibition of Lyn (SFK family) or activation of Rho‐associated protein kinase (ROCK, a serine‐threonine kinase) 23 . At a very high dose (≥50 mg/kg), dasatinib increases vascular leakage in the unchallenged small intestine and spleen of mice via activation of ROCK and subsequent myosin light chain phosphorylation inside endothelial cells, leading to downregulation of VE‐cadherin and other associated junctional molecules 7,24 . In agreement with this, our pilot study demonstrated that high doses of dasatinib (25 and 50 mg/kg) induced severe intestinal bleeding in mice within 24 h but no vascular leakage was observed in the wound area (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if treatment duration is prolonged periods of time, the health gaining effects must outweigh potential side-effects. For example: Dasatinib can cause gastrointestinal bleeding and liver damage ( Liu et al, 2020 ). A possible approach to avoid this may be combining medication, i.e., handling rapamycin-caused glucose dysmetabolism with metformin ( Blagosklonny, 2019 ).…”
Section: Discussionmentioning
confidence: 99%